Back Cover: Sugar‐based Molecular Computing by Material Implication (Angew. Chem. Int. Ed. 28/2014). Issue 28 (16th June 2014) - Elstner, Martin; Axthelm, Jörg; Schiller, Alexander
<x xml:space="preserve">Abstract</x> Molecular logic and computing are based on the principles derived by Prof. Frege (University of Jena, 1848–1925). A. Schiller and co‐workers present in their Communication on page 7339 ff. a method to integrate an (in principle) unlimited number of molecular logic gates to construct complex circuits on microtiter plates. Using a fluorescent boronic acid fructose probe and the FALSE operation, an external wiring algorithm translates the fluorescent output from one gate into a chemical input for the next gate by pipetting steps.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>